The Influence of Price and Income on Fast Food Consumption in Islam (Case Study of Postgraduate Students in Islamic Economics Class A and B Class of 2022 State Islamic University Sjech M. Djamil Djambek Bukittinggi) - Amsah Hendri Doni; Fifa Alfiona; Tifany Yeldi Astuti; Melisa Anggreni; Zelfia Khairani; Elvi Nasriandani; Restika Restika; Al - Amin (Departement of Mathematics Education, 2023)
Changes in the quantity demanded due to changes in price occur through two complementary effects, namely the substitution effect and the income effect. This effect also affects the theory. behavior _ k consumption in islam and based on law Islam. Difference this concern score core in the lower theory, motive and purpose consumption, technique choice and allocation budget consumption. This research uses quantitative methods. Data processing and hypothesis testing used SPSS version 18. This research was conducted on Postgraduate Students in Islamic Economics Class A and B Class of 2022. Sampling used Simple Random Sampling. The total population of Postgraduate students in Islamic Economics Classes A and B Class of 2022 is 35 people. The results of this study, obtained several conclusions which are briefly presented as follows. Based on the F test, the independent variables consisting of (Price and Income) together have a positive and significant effect on the dependent variable (Consumption).